2017
DOI: 10.3390/jfmk2020016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stochastic Resonance on Sensorimotor Performance during Exercise-Induced Muscle Damage

Abstract: Abstract:The aim of this study was to assess the effects of stochastic resonance (SR) stimulation on sensorimotor performance during an episode of exercise-induced muscle damage (EIMD). Thirty four men (age: 21.3 (±2.6) years; height 1.78 (±0.06) m; body mass 72.3 (±7.4) kg (mean (±SD)) gave their informed consent to participate in this study.Sensorimotor performance (error in replicating a target force) of the knee flexors was assessed prior to, and at 0.5 and 48 h after (i) a treatment condition involving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Effects of stochastic resonance were also studied in the context of sensorimotor performance during exercise induced muscle damage. Gleeson (2017) studied how application of mechanical vibrations to the biceps femoris muscle influences sensorimotor performance of target force replication (Gleeson, 2017). The study showed that subthreshold mechanical vibrations compensate the negative effects of muscle damage and suggested that more efficient means of delivering stochastic resonance (e.g., functional electrical stimulation) would be needed to improve the effectiveness to enhancing sensorimotor performance under adverse conditions of exercise stress.…”
Section: Stochastic Resonance: When Noise Becomes An Allied To the Brainmentioning
confidence: 99%
“…Effects of stochastic resonance were also studied in the context of sensorimotor performance during exercise induced muscle damage. Gleeson (2017) studied how application of mechanical vibrations to the biceps femoris muscle influences sensorimotor performance of target force replication (Gleeson, 2017). The study showed that subthreshold mechanical vibrations compensate the negative effects of muscle damage and suggested that more efficient means of delivering stochastic resonance (e.g., functional electrical stimulation) would be needed to improve the effectiveness to enhancing sensorimotor performance under adverse conditions of exercise stress.…”
Section: Stochastic Resonance: When Noise Becomes An Allied To the Brainmentioning
confidence: 99%